Activation of Molecular Hydrogen by Inter‐ and Intramolecular Al−N Lewis Pairs. Issue 13 (19th February 2021) - Bodach, Alexander; Nöthling, Nils; Felderhoff, Michael
Abstract: The field of frustrated Lewis pair chemistry offers many opportunities to activate molecular hydrogen, but Al−N systems have not been established yet. In this work, we describe several intermolecular classical Al−N Lewis pairs and an intramolecular ortho‐ala‐aminoarene for the activation of molecular hydrogen. Their ability was investigated using the isotope exchange reaction from HD to H2 and D2 . The herein studied intermolecular Lewis pairs were based on alkylalanes and N‐methyldiphenylamine, while the intramolecular Lewis pair was ( o ‐TMP−C6 H4 )AlH2 ((2‐(2, 2, 6, 6‐tetramethyl‐piperidin‐1‐yl)phenyl)‐aluminium dihydride). The activation of molecular hydrogen was carried out in toluene under mild conditions and monitored by 1 H and 2 H NMR spectroscopy. Furthermore, the Al−N interaction has been probed by 27 Al NMR and crystallographic studies. Additionally, the crystal structure of pure Al i Bu3 was determined. These studies may attribute the pronounced reactivities of these Al−N compounds to elongated Al−N bond lengths. Abstract : Several intermolecular classic Al−N Lewis pairs of alkylalanes and N‐methyldiphenylamine, as well as an intramolecular ortho‐ala‐amino‐arene, were tested for their ability to activate hydrogen by studying the isotope exchange reaction of HD and successive 1 H and 2 H NMR spectra. The Al−N interaction has been probed by NMR spectroscopy and crystallographic studies, including those of pure Al i Bu3 .